Neurotoxins: Expanding Uses of Neuromodulators in Medicine—Major Depressive Disorder. (November 2015) - Magid, Michelle; Keeling, Brett H.; Reichenberg, Jason S.
Abstract : Background: Botulinum toxin A (BTA) is one of the most diversely used medications of the 21st century and is now being researched as a treatment for major depressive disorder (MDD). Methods: The authors performed a literature search of PubMed, Web of Science, and the Cochrane Register of Controlled Trials. The primary investigators of the studies were contacted for additional unpublished data. Results: The authors identified 5 studies that met the criteria of using BTA in the treatment of MDD. All studies showed significant reduction in depressive symptoms with BTA injected into the glabellar muscles. In a pooled analysis, botulinum toxin ( n = 59) vs placebo ( n = 75) had a –47% vs –16% reduction in self-rated depression scores ( P < 0.0001) and a –46% vs –15% reduction in expert-rated depression scores ( P < 0.0001), respectively. Adverse reactions were mild (temporary headaches and local irritation immediately after injection) and did not differ between active group (13.6%) and placebo group (9.3%) ( P = 0.44). Conclusions: Botulinum toxin injections in the glabellar frown muscles have been associated with a significant improvement in depressive symptoms. Given the prevalence of MDD, the promising results of preliminary trials, and the excellent tolerability of this treatment intervention, larger studies are warranted. Abstract : Supplemental Digital Content is available in the text.